Astrocyte senescence: Evidence and significance. Issue 3 (27th February 2019) - Cohen, Justin; Torres, Claudio
Abstract: Astrocytes participate in numerous aspects of central nervous system (CNS) physiology ranging from ion balance to metabolism, and disruption of their physiological roles can therefore be a contributor to CNS dysfunction and pathology. Cellular senescence, one of the mechanisms of aging, has been proposed as a central component of the age dependency of neurodegenerative disorders. Cumulative evidence supports an integral role of astrocytes in the initiation and progression of neurodegenerative disease and cognitive decline with aging. The loss of astrocyte function or the gain of neuroinflammatory function as a result of cellular senescence could have profound implications for the aging brain and neurodegenerative disorders, and we propose the term "astrosenescence" to describe this phenotype. This review summarizes the current evidence pertaining to astrocyte senescence from early evidence, in vitro characterization and relationship to age‐related neurodegenerative disease. We discuss the significance of targeting senescent astrocytes as a novel approach toward therapies for age‐associated neurodegenerative disease.